PROFESSIONAL DEVELOPMENT OF SECONDARY AND JUNIOR STAFF OF HEALTH CARE INSTITUTIONS - GRYNKO, Tetyana; GVINIASHVILI, Tetyana; PINDICH, Anastasya (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article summarizes approaches to determining the essence of professional development of personnel. The role of middle and junior medical personnel in the health care system is defined as an important component of ensuring the efficiency and effectiveness of its functioning. The state and global trends in the development of nursing are outlined. The problems and shortcomings of the implementation of continuous professional development of medical personnel in Ukraine have been identified. A research of the successful foreign experience of the professional development of nurses, in particular according to the European and American models, was conducted. Useful tools for organizing continuous professional development based on competencies borrowed from foreign experience are highlighted. The main provisions of the From Novice To Expert theory, developed by P. Benner, are highlighted. In order to improve the system of continuous professional development of middle and junior medical personnel, it is proposed to apply the author's model P. Benner "Clinical ladder as a way of professional advancement" in health care institutions of Ukraine.
Keywords: staff development; middle and junior medical staff; healthcare facilities; continuous professional development of medical staff; foreign experience